Fontes de lipídios e classe sexual no confinamento de ovinos - Homem, Antonio Carlos; Ezequiel, Jane Maria Bertocco [UNESP]; Fávaro, Vanessa Ruíz; Perez, Henrique Leal [UNESP]; Almeida, Marco Túlio Costa [UNESP]; Paschoaloto, Josimari Regina [UNESP]; D'Áurea, André Pastori; Carvalho, Vanessa Barbosa [UNESP]; Faleiros, Bruno Nocera (Universidade Estadual de Londrina, 2015)
The objective of this study was to evaluate the effects of lipid sources in the diet and sexual condition on carcass traits, non-carcass components and muscle chemical composition of feedlot sheep. Twenty male and 20 female Dorper cross St Ines sheep, with initial weight of 19.5±2.8 kg were fed on a diet consisting of 40:60 roughage: concentrate ratio. Five rations were tested, the control ration contained no additional lipids whereas the four test rations contained lipids sourced from either sunflower grains, peanut kernels, crude peanut oil or protected fat. A randomized complete block design in factorial scheme was used (2 sexes × 5 lipid sources). The animals were slaughtered at an average of 37.5±0.8 kg. There was no effect of lipid source on any of the carcass variables measured (P> 0.05). Males had higher carcass weights and true yields than females. Females, however, had higher percentages of omental+mesenteric+pelvic fat (8.8 vs 6.4%), subcutaneous fat thickness (4.51 vs 2.23 mm), and intramuscular lipid concentrations (5.06 vs 3.77 g 100g-1 of muscle). Therefore, it appears that females are more inclined to fat deposition when slaughtered at the same weight as males. Further research is required to determine if it is possible to include these lipid sources in feedlot rations without changing the production and composition of sheep meat.
Lipid sources in the diets and sexual condition of feedlot sheep
Keywords: Carcass; Peanut; Peanut oil; Protected fat; Sexual condition; Sunflower